Reverse osmosis design with IMS design software to produce drinking water in Bandar Abbas, Iran - Nafiseh Aghababaei (Journal of Applied Research in Water and Wastewater, 2017)
Reverse osmosis (RO) has proven to be an efficient technique for desalination of seawater, brackish water, and reclaimed wastewater. However, the performance of RO desalination is sensitive to its design parameters and operating conditions. The purpose of this study was to modeling the removal of total dissolved solids (TDS) and Rejection of different ions are reported from water of city of Bandar Abbas. The main purpose of this work was the prepared drinking water intrusion model. In this study, a design method based on a simulation technique has been developed for optimizing RO desalination systems. The design is made with the use of Hydranautics design software version 2011. In this paper main focus is on the design part with software. The desalinated water obtained from reverse osmosis at a pressure of 1.2 MPa showed rejections of approximately 88.49 % for SO4 2 −, 61.42 % for TDS, 70.34 for Cl- and 50.85 for Na+. It shows that software gives accurate design with least possible error and user friendly so world while accepted. Blended water, produced by mixing groundwater and surface, was proposed to optimize the produce drinking water with a recovery rate of 95 %. Reverse osmosis is an excellent alternative for the supply of water in Bandar Abbas.